Interventional pain management for a patient with chronic post-traumatic headaches after a traumatic brain injury - Hasoon, Jamal; Urits, Ivan; Berger, Amnon A.; Viswanath, Omar (Anestezjologia Intensywna Terapia, 2021)
Traumatic brain injuries (TBI) and chronic post-traumatic headaches (PTH) have affected many military personnel. The increasing use of improvised explosive devices have made blast- and explosive-related head injuries more common than in previous wars [1, 2]. Data from Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn demonstrate that a significant portion of military TBIs are caused by blast-related injuries [3, 4]. From 2000 to 2016 more than 350,000 military service members were diagnosed with a TBI [4]. Military troops are at greater risk of developing PTH from head injuries that arise during deployment to combat zones. These patients can be extremely challenging because they often suffer from comorbid conditions including depression and post-traumatic stress disorder (PTSD). Additionally, there is a lack of high-quality studies on the treatment of PTH [5]. This brief report describes a patient who suffered from chronic PTH after sustaining a mild TBI, and our results with greater occipital and auriculotemporal nerve blocks.